2022
DOI: 10.3390/ijms232214057
|View full text |Cite
|
Sign up to set email alerts
|

The SARS-CoV-2 Delta-Omicron Recombinant Lineage (XD) Exhibits Immune-Escape Properties Similar to the Omicron (BA.1) Variant

Abstract: Recently, a recombinant SARS-CoV-2 lineage, XD, emerged that harbors a spike gene that is largely derived from the Omicron variant BA.1 in the genetic background of the Delta variant. This finding raised concerns that the recombinant virus might exhibit altered biological properties as compared to the parental viruses and might pose an elevated threat to human health. Here, using pseudotyped particles, we show that ACE2 binding and cell tropism of XD mimics that of BA.1. Further, XD and BA.1 displayed comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…These co-infections may not only have clinical relevance 30 , but also represent potential recombination events. For example, the BA.1 wave showed the highest prevalence of co-infections in our dataset and incidentally introduced numerous recombinants, including those formed from Delta and BA.1 4244 . Ultimately, the use of long reads is uniquely suited for distinguishing co-infections from these recombinant cases as well as other sources of intra-host variation of the virus that have been described 31 .…”
Section: Discussionmentioning
confidence: 97%
“…These co-infections may not only have clinical relevance 30 , but also represent potential recombination events. For example, the BA.1 wave showed the highest prevalence of co-infections in our dataset and incidentally introduced numerous recombinants, including those formed from Delta and BA.1 4244 . Ultimately, the use of long reads is uniquely suited for distinguishing co-infections from these recombinant cases as well as other sources of intra-host variation of the virus that have been described 31 .…”
Section: Discussionmentioning
confidence: 97%
“…Following mutations in the virus genome, new variants emerged. To date, the WHO defines five variants of concern (VOCs), Alpha, Beta, Gamma, Delta, and Omicron, which have all spread swiftly on a global scale ( 1 4 ). VOCs of SARS-CoV-2 can cause serious diseases, increase infectivity, reduce any viral neutralization via antibodies as elicited by prior infections or vaccinations, and limit the efficacy of vaccine immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, 15 mutations are in the receptor binding domain (RBD), which is over 2-fold the number in the Delta variant ( 7 9 ). At the time of manuscript submission, the newly emerged Omicron variant had five distinct subvariants (with sublineages): BA.1, BA.2, BA.3, BA.4, and BA.5 ( 4 ). An increase in the number of mutations also increases the transmission rate of the virus.…”
Section: Introductionmentioning
confidence: 99%
“…Although the Omicron RBD carries 15 mutations, there is no gain in ACE2 binding affinity in comparison to the wild-type RBD [40]. Recently emerged Delta-Omicron recombinant XD variant also displays immune escape abilities similar to the Omicron BA.1 variant [41,[42][43][44]. By analyzing the differences in the binding pattern between the wild type and Omicron (B.1.1.529) variant with ACE2 revealed that the key substitutions at K417N, G446S, Q493R, and Q498R in the B.1.1.529 RBD causes additional interactions with ACE2 receptor [45].…”
Section: Introductionmentioning
confidence: 99%